A manifesto for planning after the coronavirus: Towards planning of care. (August 2020) - Jon, Ihnji
The COVID-19 crisis upended the status quo of our everyday life. The rising discourse in the midst of this pandemic is 'human guilt' (e.g., 'we are the virus!'), reviving the dark side of neo-Malthusian environmentalist ideology. While the pandemic should be considered a wake-up call for us to drastically rethink our relationship with nature, planning discipline cannot resign itself from its power and responsibility to make a difference in human and nonhuman lives. So, here I ask: How can we carefully reposition 'human intervention' in the aftermath of this 'human guilt', without nullifying the hopeful spirit and our belief in the power of planning? Inspired by Tronto/ Lawson's geographies of care and Dewey-an pragmatism, this essay calls for the rise of 'planning of care'. Planning of care not only recognises humans' interdependency on one another, but also acknowledges cities' on-going, dialectic relationship with their natural surroundings.